Diretrizes para formação de professores espírito-santenses na antessala da ditadura do Estado Novo (1930-1937) - Lauff, Rafaelle Flaiman (2018)
This research investigates educational policies and elementary school teacher education during the transition from the New School (1828-1930) to the educational reforms by interventionist governor João Punaro Bley in Espírito Santo after the 1930 Revolution that preceded the New State dictatorship. We seek to identify the policies designed for teacher education and teaching practice as well as their developments in Espírito Santo, in addition to outlining what was presented as innovative pedagogy and educational policies. Permanent and provisional policies during the federal intervention are examined in terms of their commonalities and differences in relation to those that came just before, during the New School. We look at the strategies used to define the remodeling of teaching after the 1930 Revolution overthrew the Government staff in charge of the capixaba public education reform that was based on the precepts of the Active School. The historiography is built upon a dialogue with Carlo Ginzburg (2001, 2002, 2003, 2007), Marc Bloch (2001) Enrico Castelnuovo, Marco Poni (GINZBURG; CASTELNUOVO; PONI, 1989) and Roger Chartier (1990, 1991). The sources we resorted to include government mail; Education Office reports; local, national and international newspaper stories; Inspector reports, the legislation, decrees and bibliographic material. The set of sources examined included documents such as government messages, Secretariat reports, materials published in the local periodical press, inspection reports, laws, decrees and bibliographic material. Guidelines for civics, Catholic morality and new pedagogy were identified. The goal of unification of normal teaching sought the construction of the Brazilian homeland, through the formation of the new man. In Espírito Santo, educational agents, teacher educators, made clear their choice for the foundations of Catholicism. Nuances between old and new could be perceived in the pedagogical models adopted in the schools, which did not totally abolish the old methods of teaching, that is, the old pedagogical procedures were mixed with the so-called new ones. The normal course was expanded to the southern region of Espírito Santo, with poles in the cities of Cachoeiro de Itapemirim, Alegre and Muqui. The first Congress of Pedagogical Improvement happened in the city of Alegre, searching in an authoritarian way, the standardization of teaching procedures based on an intuitive-active pedagogy. The Bley Government preferred not to bring technicians from outside the State to prepare the local teaching, instead sent some teachers to learn the pedagogical innovations in São Paulo and Rio de Janeiro. It also prioritized the training through individual reading of the teaching staff, creating a section entitled Educational Life in the newspaper Diário da Manhã and the Journal of Education, equipping the Radiating and Circulating Libraries with publications indicated by Lourenço Filho referring to the New School, however there was low demand of teachers by these readings. The expansion of normal education was accompanied by a teacher training focused on practicality and with theoretical emptying.